The wonder boy of whistle stop eaudiobook A novel. - Flagg, Fannie (Random House Audio, 2020)
NEW YORK TIMES BESTSELLER • A heartwarming novel about secrets of youth rediscovered, hometown memories, and the magical moments in ordinary lives, from the beloved author of Fried Green Tomatoes at the Whistle Stop Cafe “A gift, a blessing and a triumph . . . celebrates the bonds of family and friends—and the possibilities of recovery and renewal.”— The Free Lance–Star Bud Threadgoode grew up in the bustling little railroad town of Whistle Stop with his mother, Ruth, church-going and proper, and his Aunt Idgie, the fun-loving hell-raiser. Together they ran the town’s popular Whistle Stop Cafe, known far and wide for its fun and famous fried green tomatoes. And as Bud often said of his childhood to his daughter Ruthie, “How lucky can you get?” But sadly, as the railroad yards shut down and Whistle Stop became a ghost town, nothing was left but boarded-up buildings and memories of a happier time. Then one day, Bud decides to take one last trip, just to see what has become of his beloved Whistle Stop. In so doing, he discovers new friends, as well as surprises about Idgie’s life, about Ninny Threadgoode and other beloved Fannie Flagg characters, and about the town itself. He also sets off a series of events, both touching and inspiring, which change his life and the lives of his daughter and many others. Could these events all be just coincidences? Or something else? And can you really go home again?